1986
DOI: 10.1136/bmj.293.6554.1053
|View full text |Cite
|
Sign up to set email alerts
|

Sural nerve oxygen tension in diabetes.

Abstract: Peripheral nerve oxygen tensions were assessed in vivo by using microelectrodes to measure endoneurial oxygen tension in exposed sural nerve. In 11 diabetic patients with chronic sensorimotor neuropathy the mean endoneurial oxygen tension was 39 7

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
112
0
1

Year Published

1988
1988
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(123 citation statements)
references
References 7 publications
10
112
0
1
Order By: Relevance
“…Additionally, we also demonstrate a reduction in luminal size which has not been demonstrated previously, though these studies were performed in patients with mild and established neuropathy [12][13][14]. This is important as it provides a morphological basis for an early reduction in nerve blood flow and endoneurial oxygenation [7].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Additionally, we also demonstrate a reduction in luminal size which has not been demonstrated previously, though these studies were performed in patients with mild and established neuropathy [12][13][14]. This is important as it provides a morphological basis for an early reduction in nerve blood flow and endoneurial oxygenation [7].…”
Section: Discussionsupporting
confidence: 73%
“…Metabolic [3] and vascular [4][5][6][7] factors play an important role in its pathogenesis. Detailed neurophysiological studies in diabetic patients have shown that demyelination precedes axonal loss and that the latter may be responsible for the symptoms [8].…”
Section: Introductionmentioning
confidence: 99%
“…Similar subclinical functional indicators are found in newly-diagnosed diabetic patients [5,6]. Endoneurial hypoxia and reduced blood flow are also present in patients with established neuropathy [7][8][9]; therefore it is likely that neurovascular effects play a major role in the aetiology of this diabetic complication.…”
supporting
confidence: 56%
“…Sciatic nerve endoneurium is hypoxic in experimental diabetes [1,36,39], as is the sural nerve in neuropathic patients [7]. This provides one potential stimulus for endothelial ET synthesis and release [27].…”
Section: Discussionmentioning
confidence: 99%
“…these are not fully known in detail. A plausible (but arguable) current view is that vascular dysfunction, which causes decreased nerve blood flow and results in endoneurial hypoxia sufficient to damage nerve fibres (Newrick et al, 1986;Low et al, 1987;Cameron et al, 1991b;Tesfaye et al, 1992), provides the most important contribution to the aetiology of diabetic neuropathy.…”
Section: Introductionmentioning
confidence: 99%